The choroid in aging and disease - Mullins, Robert F. (Henry Stewart Talks, 2016)
Age-related Macular Degeneration (AMD), Drusen, Atrophy, Vascular changes, Proteomics of choroidal thinning, Fibrosis, CD34, C-reactive protein accumulation, Complement cascade: Membrane Attack Complex (MAC)